GAMBARAN KEMAMPUAN SAINS ANAK USIA 5-6 TAHUN DI KELOMPOK B1 TK DHARMA PERTIWI KECAMATAN BAGAN BATU KABUPATEN ROKAN HILIR - Siregar, Elvianna; Zulkifli N, Zulkifli N; Nurlita, Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak :This research intended how to know ability children five and six years old science in kindergarden Darma Pertiwi. The data techniques observation and data analysis with a percentage formula. The results obtained the fourth indicator the highnest percentage getting in third indicator. The children can to solved problem science the children solved the story about the science games, with percentage 88,33% while the fourth indicator the children solved the story about the science games 81,66% beside on higher category. It cat be concluded the ability of science five and six community of B1 Kindergarden Dharma Pertiwi more higher the average 71,92%. The keywords of science ability children.Keywords: the ability ofscience, student, lecture